IMPLEMENTATION OF ISLAMIC DA’WAH IN THE MALAYSIAN ARMED FORCES: THE EXPERIENCE OF THE ARMED FORCES RELIGIOUS CORPS - Jalal, Burhanuddin; Ghani, Sayuti Ab; Ismail, AmnahSaayah (The journal of contemporary issues in business and government, 2021)
Efforts to implement da’wah in the organisation must be made in an orderly and planned manner to achieve good results. The Ministry of Defence Malaysia, established the Armed Forces Religious Corps(Malay: Kor Agama Angkatan Tentera, KAGAT) in 1985, to build an appreciation of Islam among the military to form the strength of personnel’s, both spiritually and mentally, to provide a strong combat force to defend religion, race and country. This paper will explain the da’wahefforts made by KAGAT in the way ofwasatiyyahto have a significantimpact on the appreciation of Islam among the personnel of the Malaysian Armed Forces as well as the effectsof Islamic da’wahin Malaysia. Library research, questionnaire methods, interviews and observations were used to obtain research data. The findings of the study show that KAGAT’s experience in the implementation of da’wah throughwasatiyyahin military organisations and face various of challenge can be used as a useful guideline for da’wah organisations and preachers in Malaysia.